Risk-based contaminated land investigation and assessment - Petts, Judith (Wiley, 1997)
This book provides a unique, practical guide to the effective conduct of risk assessments for contaminated sites. The risk-based approach requires recognition of site investigation as a component of (not merely an adjunct to) risk assessment and a systematic gathering of quality data relevant to making judgements about risks. This is an integrated and multidisciplinary subject. The book provides an understanding of the regulatory and social context in which contaminated land risks are managed; the interdisciplinary requirements, as well as the methodologies and their limitations for investigation and assessment. The book has been written to complement developing guidance and requirements in the United Kingdom, but with international comparisons. The issues which underpin effective contaminated land risk assessment are universal.